Geometrically isomeric [Ir(iqbt)(ppy)(hpa)] complexes with differential molecule orientations for efficient near-infrared (NIR) polymer light-emitting diodes (PLEDs). Issue 36 (6th September 2021) - Li, Wentao; Liu, Jiaxiang; Wang, Baowen; Hou, Siyu; Lü, Xingqiang; Fu, Guorui; Wong, Wai-Yeung
Abstract : Based on geometrical isomerisation of [Ir(C^N 1 )(C^N 2 )((N^O))]-tris-heteroleptic Ir(iii )-complexes, the augmented transition dipole transition (TMD) with a preferential horizontal orientation, which is beneficial for their NIR-phosphorescence, is reported. Abstract : Based on geometrical isomerisation of [Ir(C^N 1 )(C^N 2 )(N^O)]-tris-heteroleptic Ir(iii )-complexes, the augmented transition dipole transition (TMD) with a preferential horizontal orientation, beneficial for their photo-excited and electroluminescent NIR-phosphorescence, is reported.